2016
DOI: 10.1103/physrevb.94.064432
|View full text |Cite
|
Sign up to set email alerts
|

Featureless quantum insulator on the honeycomb lattice

Abstract: We show how to construct fully symmetric, gapped states without topological order on a honeycomb lattice for S = 1/2 spins using the language of projected entangled pair states (PEPS). An explicit example is given for the virtual bond dimension D = 4. Four distinct classes differing by lattice quantum numbers are found by applying the systematic classification scheme introduced by two of the authors [S. Jiang and Y. Ran, Phys. Rev. B 92, 104414 (2015)]. Lack of topological degeneracy or other conventional form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 38 publications
7
39
0
Order By: Relevance
“…On the other hand, on the honeycomb lattice, we find no anomalies for the symmetries listed above. Again, this is consistent since a trivial symmetric gapped state on the honeycomb lattice has been recently constructed [13,14]. The treatment of lattice symmetries as internal symmetries for the purpose of anomaly computation is consistent with Ref.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, on the honeycomb lattice, we find no anomalies for the symmetries listed above. Again, this is consistent since a trivial symmetric gapped state on the honeycomb lattice has been recently constructed [13,14]. The treatment of lattice symmetries as internal symmetries for the purpose of anomaly computation is consistent with Ref.…”
Section: Introductionsupporting
confidence: 84%
“…Hence, in this case there are neither emergent nor intrinsic anomalies. The absence of an intrinsic anomaly is in agreement with the existence of a trivial gapped state on the honeycomb lattice [13,14]. Let us now discuss possible consequences of the absence of emergent anomalies.…”
Section: B S = 1/2 Honeycomb Latticesupporting
confidence: 68%
“…For instance, when SG involves translation symmetries in two and higher spatial dimensions d, our construction related to H d+1 (SG, U (1)) clearly demonstrates so-called "weak topological indices", whose physical origin is related to lower dimensional SPT phases. As a concrete example, previously we demonstrated that there are 4 distinct featureless Mott insulators on the honeycomb lattice at half-filling 25 . These distinct featureless Mott insulators now can be nicely interpreted as the consequence of two weak topological indices.…”
mentioning
confidence: 94%
“…(See Ref. [34][35][36] for a tensor-network construction of a state with similar transformation properties.) In the thermodynamic limit N → ∞, a band insulator would transform trivially under all point group operations for both N/2 odd and N/2 even, i.e., independently of how the thermodynamic limit is approached.…”
mentioning
confidence: 99%